Revolutionizing Wound Healing: Unleashing Nanostructured Lipid Carriers Embodied with Herbal Medicinal Plant - Jain, Aditya; Yadav, Shikha; Khan, Javed (Current Pharmaceutical Biotechnology, 2025)
Wound healing is crucial for maintaining skin integrity and preventing complications from external threats. Various plants, such as Achillea millefolium, Aloe vera, Curcuma longa, Calendula officinalis, Camellia sinensis, Azadirachta indica, and Plantago, have demonstrated wound healing capabilities and have been used in herbal medicine for wound care. NLCs are second-generation lipid nanoparticles, blending solid and liquid lipids to improve medication loading and limit leakage. NLCs have been used in various applications, including cosmeceuticals, chemotherapy, gene therapy, and brain targeting. Wound healing is divided into four stages: hemostasis, inflammatory response, proliferation, and remodeling. Factors such as age, gender, chronic disorders, and local agents like infections can affect recovery. These plants' anti-inflammatory, antioxidant, and antibacterial activities have demonstrated potential in wound healing. Combining herbal medicinal plants and nanostructured lipid carriers (NLCs) can revolutionise wound treatment and improve overall healthcare outcomes.
Keywords: Wound healing